(3EOGQI GdGfJGL h GdYedjGJ (B:s (3eQJcRGJ cejI h eYQajI (B/s - (3GddGej, ZSGf bGSe OGhOs; (3TcQhdj, GdHjGJj CejQI s ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2008)
(3jSYi GdcJGH Edi JbOje EZfGA eYQaj hYedj djde GdbGQF HGdeaGgje hGdJWHjbGJ GdMOjKI dEOGQI fTGWGJ GdYedjGJ aj GdefXeI hJWHjbGJgG GdYedjI LQGA GSJjYGH hXGFagG eaGgjekG hJbfjkG hHeG JSge aj JbOje age eJcGed dEJNGP GdbQGQGJ GdJTZjdjI HTcd eJcGed hUGFH MjK GdeOGNd hGdELQGAGJ hGdJeGQjf hGdMGdGJ GdYedjI GdJj JfGSH cd aYGdjI Ch hXjaI ajgG(B. (3aVdkG Yf eSGgeI eaQOGJg hehGVjYg aj EKQGA GdecJHI GdYQHjI HeQLY jajO WdHI GdOQGSGJ GdChdjI hGdYdjG aj eLGdGJ EOGQI GdEfJGL hGdYdejGJ dGNJUGUGJ EOGQI GdCYeGd hGdEOGQI GdUfGYjI HZjI JfejI eDgdGJge hbOQGJge ddJYGed eY hXGFa GdEfJGL hGdYedjGJ aj GdeLGdGJ GdJWHjbjI(B. (3GLJgO GdeDdaGf dGcSGH eDdage UaI GdeYGUQI YHQ EWdGYge Ydi CMOK GdeUGOQ ef COHjGJ hOQGSGJ eJNUUI MOjKI ef eLGdGJ EOGI GdEfJGL hGdYedjGJ djchf eVehf LgOge GdeJhGVY efGSHkG dEYOGO YGedjf hOGQSjf eDgdjf ddGdJMGb Edi ejGOjf GdEfJGL hab GdJhLgGJ GdLOjOI GdefGSHI ddMGb HeSjQI GdYde hGdeYQaI hGdJWhQ hYUQ GdeYdheGJjI hGdJLOO(B. (3jJVef GdcJGH CMO YTQ aUhdkG EP jJfGhd GdaUd GdChd eONd Edi EOGQI GdEfJGL hGdYedjGJ ehVi GdeaGgje hGdJWhQ hGdCOhGQ hGdGSHbjGJ GdJfGaSjI, hCge ebGjjS GdEfJGLjI, hJVef GdaUd GdKGfj JNWjW hJWhjQ hGdJUeje GdefJhL, hJMUU GdaUd GdKGdK dehVhY GNJjGQ ehbY GdeUfY, GfaQO GdaUd GdQGHY ddJQJjH GdOGNdj ddeUfY hehGRfI NW GdJLejY, hQcR GdaUd GdNGeS dJcfhdhLjG GdYedjGJ aj eLGdGJ GdJUeje hGdEfJGL hGdeYdheGJ, hJfGhd GdaUd GdSGOS JNWjW GdWGbI hGSJQGJjLjGJgG hNWhGJ bjGSgG eY CeKdI eMdhdI, hTed GdaUd GdSGHY dGSJQGJjLjGJ GdJNWjW GdELeGdj eY JWHjbGJ YedjI, hGMJhi GdaUd GdKGef dfXGe JNWjW GdGMJjGLGJ ef GdehGO heONdGJg heNQLGJg hCSGdjH JMOjO MLe GdOaYI dCZQGV JWHjb gPG GdfXGe, hHjf GdaUd GdJGSY ehVhY LOhdI GdYedjGJ GdJTZjdjI, hGfaQO GdaUd GdYGTQ ddUjGfI hGdeYhdjI hCNjQkG GMJhi GdaUd GdMGOj YTQ EOGQI GdLhOI GdTGedI hJMSjf GdYedjGJ(B.s
Keywords: (3EOGQI GdEfJGLs; (3HMhK GdYedjGJs